1999
DOI: 10.1023/a:1008148803544
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The purpose of this study was to evaluate the effect of pH on the extraction of protein nitrogen from Atriplex lampa leaves (Moquin) Dietrich. The chemical characterization of the dry matter indicated the following (g/100 g): protein, 26.93; ash, 21.80; ether extract, 4.65; dry matter, 37.30; sodium, 6.05; and calcium, 0.41. Non-critical values were obtained for saponins and nitrates. The high concentration of oxalic acid (8.52 g/100 g), together with elevated salt content account for the low palatability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 2 publications
2
6
0
Order By: Relevance
“…The amount of protein extracted increased dramatically from a pH of 8 to 10.5 before leveling off. Similar trends have been seen in other types of biomass [10][11][12][13][14][15][16]. Most proteins have an acidic isoelectric point, the pH at which the protein will have no net charge and therefore be the least soluble in a polar medium.…”
Section: Composition Analysissupporting
confidence: 69%
See 2 more Smart Citations
“…The amount of protein extracted increased dramatically from a pH of 8 to 10.5 before leveling off. Similar trends have been seen in other types of biomass [10][11][12][13][14][15][16]. Most proteins have an acidic isoelectric point, the pH at which the protein will have no net charge and therefore be the least soluble in a polar medium.…”
Section: Composition Analysissupporting
confidence: 69%
“…Protein yields varied considerably depending upon the types of biomass, generally resulting in high yields of protein from grains and moderate to low yields from leaf proteins. Studies with Atriplex leaves obtained only 41% of the total protein, while a pilot plant extracting proteins from alfalfa obtained 47% of the total protein [15,16]. In general, it appears that simple extractions are not sufficient to obtain complete protein recovery from leafy biomass.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…21,70,81,123,[215][216][217][218][219][220][221] Related work on producing leaf protein from terrestrial biomass biorefineries for human nutrition may also be applicable to algae biorefineries. 7,222,223 The quality (and thus value) of algal protein for human or animal consumption depends on the amino acid composition, in particular the respective concentration of limiting amino acids, palatability and digestibility of the proteins, and the amount of non-protein nitrogen and other potential anti-nutritional components.…”
Section: Protein As the Basis For Food And Feedmentioning
confidence: 99%
“…In general, protein from algae shows good nutritional characteristics, 216,224,225 and a typical amino acid composition of the three major genera discussed in this review is shown in Table 8. 7,222,223 Integrating food or feed uses of fractionated or extracted algae will need to be tested to ensure that these industrially processed residues remain a good nutritional…”
Section: Protein As the Basis For Food And Feedmentioning
confidence: 99%